A brief account of the province of Pennsylvania, lately granted by the King, under the great seal of England, to William Penn and his heirs and assigns - Penn, William, 1644-1718 (Printed for Benjamin Clark, 1681)
1681 Pamphlet entitled "A Brief Account of the Province of Pennsylvania, lately granted by the King to William Penn and his heirs and assign." Included were the patent, and the King's declaration to the inhabitants of Pennsylvania.